Managing Government Compensation and Employment : Institutions, Policies, and Reform Challenges. (Policy Papers; Policy Paper ;, 2016)
Government compensation and employment policies are important for the efficient delivery of public services which are crucial for the functioning of economies and the general prosperity of societies. On average, spending on the wage bill absorbs around one-fifth of total spending. Cross-country variation in wage spending reflects, in part, national choices about the government's role in priority sectors, as well as variations in the level of economic development and resource constraints.